"Backdoor Induction" of Chirality: Trans‐1, 2‐cyclohexanediamine as Key Building Block for Asymmetric Hydrogenation Catalysts. Issue 11 (27th December 2018) - Opačak, Saša; Kokan, Zoran; Glasovac, Zoran; Perić, Berislav; Kirin, Srećko I.
Abstract : This paper describes the synthesis and characterization of21 chiral monodentate ligandsL, assembled of three building blocks utilizing amide bonds: a metal binding triphenylphosphine, a chiral cyclic diamine and an additional substituent for fine‐tuning the steric and/or electronic properties. Cis square‐planar metal complexes of Rh I and Pt II withML2 stoichiometry have been prepared and characterized by spectroscopic methods (NMR, IR, UV‐Vis, CD) and DFT calculations. A key feature of the metal complexes is a prochiral metal coordination sphere and "backdoor induction " of chirality from a distant chiral source via an outer‐coordination sphere, well‐defined by aromatic stacking and hydrogen‐bonding. The rhodium complexes were used as catalysts in asymmetric hydrogenation of α, β‐dehydroamino acids with excellent yield and selectivity (up to 97 % ee ), strongly supporting the "backdoor induction " hypothesis. Abstract : Chiral information is transmitted from a distant chiral source to the prochiral coordination sphere by means of noncovalent interactions, resulting in up to 97 % ee in asymmetric hydrogenations.